Збереження екологічної стійкості національної економіки методами управління відходами - Koval, Viktor; Mikhno, Inesa (Dr. Viktor Koval, 2019)
Introduction. With the development of the economy, the amount of waste increases per capita, the number of packaging materials and the total of goods, the life cycle of which ends in the transformation into waste. Due to the slow development of waste recycling in Ukraine, the problem of their accumulation is aggravated with the increasing impact of waste landfills, which are increasing and becoming an area of increased risk, which leads to a decrease in the welfare of the population and a reduction in labor productivity. Aim and tasks. The goal of this work is to analyze the problem of waste accumulation and find ways to reduce environmental pollution as an effective way to improve the well-being of the population and increase the economic and environmental potential of Ukraine. Results. The article analyzes ways to solve the problem, taking into account the realities and positive experience of developed countries, where waste recycling has become a lucrative business and is based on the secondary use of waste and its return to the life cycle as a commodity. Identified corruption links between business and government, inefficient use of budget funds, slows down the transition to complete waste recycling, and leads to a distortion of the free market system on a competitive basis and the impossibility of foreign investors interested in running a transparent and environmentally friendly business in the field of waste recycling. The structure of the main components of household waste and the distribution of the time of their decomposition are revealed, and a diagram of the negative impact of landfills on the environment and waste management is given. The article discusses the principles of state regulation, which can improve the situation in the field of waste utilization and environmental welfare of the population. Conclusions. An analysis of modern approaches in the field of waste utilization, both liquid and solid, has shown that the main method of waste utilization is recycling as the basis of the general concept of Zerowaste for the countries with a high level of development. In Ukraine, the formation of regulators and tools to overcome the garbage crisis is slow and does not lead to significant changes. It has been substantiated that, on the basis of internalizing external effects and assisting the population in minimizing negative impacts, it is possible to achieve a reduction in overproduction of goods and services with negative external effects. Significant progress in the utilization process is possible only in the case of investment attractiveness of waste recycling business, institutional changes in tax and customs tariff legislation, macroeconomic and financial stabilization in the country.